The World Bank's Assistance to China's Transport Sector - Churchill, Anthony; Thum, Cordula (World Bank, Washington, DC, 2014)
China's economic development since the opening of its economy in the late 1970s has resulted in an eight percent average annual rate of economic growth. Key facets of this growth are rapidly increasing domestic and foreign trade as well as increasing personal mobility and consumption of energy. The deficiencies of the Chinese road and highway system have in particular created a bottleneck in China's economic development. The major objective of the China country assistance strategy (since the 1980s) was to alleviate infrastructure bottlenecks, in providing financial resources and promoting sector reforms in China. In 1997-98, the World Bank worked together with the Chinese government in completing a review of the transport sector and preparing an intermodal transport strategy. The strategy provides proposals for increasing competition and efficiency, identifies the changing patterns of demand for transport, and advances the analysis of investment needs of the sector and their financing.